2009
DOI: 10.1182/blood-2009-07-234880
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation after reduced-intensity conditioning in patients with myelofibrosis: a prospective, multicenter study of the Chronic Leukemia Working Party of the European Group for Blood and Marrow Transplantation

Abstract: From 2002 to 2007, 103 patients with primary myelofibrosis or postessential thrombocythemia and polycythemia vera myelofibrosis and a median age of 55 years (range, 32-68 years) were included in a prospective multicenter phase 2 trial to determine efficacy of a busulfan (10 mg/kg)/fludarabine (180 mg/m 2 )-based reduced-intensity conditioning regimen followed by allogeneic stem cell transplantation from related (n ‫؍‬ 33) or unrelated donors (n ‫؍‬ 70). All but 2 patients (2%) showed leukocyte and platelet eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
405
8
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(453 citation statements)
references
References 22 publications
27
405
8
13
Order By: Relevance
“…Except for allo-HSCT [7,8], the therapy of MF remains essentially palliative and is usually adjusted to the characteristics of the disease in every individual [6]. Thus, a wait-and-see approach is often adopted in asymptomatic patients, delaying treatment start until a change in the clinical situation is observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for allo-HSCT [7,8], the therapy of MF remains essentially palliative and is usually adjusted to the characteristics of the disease in every individual [6]. Thus, a wait-and-see approach is often adopted in asymptomatic patients, delaying treatment start until a change in the clinical situation is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Except for allogeneic hemopoietic stem cell transplantation (allo-HSCT) [7,8], therapy of MF remains mostly palliative and is usually adjusted to the disease characteristics in each patient [6]. In the "hyperproliferative" forms of the disease, characterized by constitutional symptoms, marked splenomegaly, leukocytosis and/or thrombocytosis, and, more rarely, aquagenic pruritus or bone pain, cytolytic treatment is usually administered [6].…”
Section: Introductionmentioning
confidence: 99%
“…RIC is associated with a lower NRM, but a higher risk of relapse, compared with standard myeloablative conditioning, and the current results suggest a qualified success (Table 1). [17][18][19][20][21] The notion of using ruxolitinib in order to reduce constitutional symptoms and splenomegaly prior to allo-SCT appears attractive. What is not known is the drug's impact on short-and long-term outcomes following allo-SCT; nor is the precise timing of allo-SCT or the role of allo-SCT-specific prognostic and predictive scores in the JAK-inhibitor era known.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kroger et al reported the results of a prospective study of RIC allogeneic HSCT as treatment for 103 patients with myelofibrosis [29]. The conditioning regimen consisted in busulfan (10 mg/kg), fludarabine and ATG.…”
Section: Myelodysplastic Syndromes and Myeloproliferative Disordersmentioning
confidence: 99%